A DESCONSTRUÇÃO DO MITO DA TRANSAMAZÔNICA A PARTIR DA ÓTICA CINEMATOGRÁFICA: TRADIÇOES INTELECTUAIS E REPRESENTAÇOES DE JORGE BODANZKY E ORLANDO SENNA, NO FILME IRACEMA: UMA TRANSA AMAZÔNICA - Gottwald Junior, Luis Alberto (2016)
This work arose from the need to think about the ways in which national cinema seeks to deconstruct a particular worldview. From this, the objective of this study was to analyze the deconstruction of the myth of a Transamazônica the progress of a military government, from the intellectual traditions and representations of Jorge Bodanzky and Orlando Senna, in Iracema: uma transa amazônica. We opted for the choice of film for its hybrid cinematic language that mixes the fictional to the documentary, it brings a denunciativo and demystifying tone of government propaganda that was the Transamazônica highway in the Brazilian dictatorial period. When doing this exercise, the filmmakers bring in their influences some elements of the New Cinema (German and Brazilian), the Italian neorealism, the Nouvelle Vague, the environmental film and a leftist militant political discourse. Through this path, appropriating from the work of filmmakers such as Jean Rouch, John Nicholas Cassavetes and Arne Sucksdorff to develop the narrative of a half-breed girl who prostitutes herself on the banks of the Trans-Amazon Highway. Methodologically, this work covers the influences and trajectories of these filmmakers and articulates every scene of the film, trying to understand the times in which the Trans Myth deconstruction appears. In this wide range of filmic readings linked to the social reality of the people who inhabited the region where they built the Trans-Amazon highway, there is the look the filmmakers about the neglect of the population, such as checking neglect appears.